A DNA Vaccine Encoding the Gn Ectodomain of Rift Valley Fever Virus Protects Mice via a Humoral Response Decreased by DEC205 Targeting - Chrun, Tiphany; Lacôte, Sandra; Urien, Céline; Richard, Charles-Adrien; Tenbusch, Matthias; Aubrey, Nicolas; Pulido, Coralie; Lakhdar, Latifa; Marianneau, Philippe; Schwartz-Cornil, Isabelle (Frontiers in Immunology, 2019)
The Rift Valley fever virus (RVFV) is responsible for a serious mosquito-borne viral disease in humans and ruminants. The development of a new and safer vaccine is urgently needed due to the risk of introduction of this arbovirus into RVFV-free continents. We recently showed that a DNA vaccine encoding eGn, the ectodomain of the RVFV Gn glycoprotein, conferred a substantial protection in the sheep natural host and that the anti-eGn IgG levels correlated to protection. Addressing eGn to DEC205 reduced the protective efficacy while decreasing the antibody and increasing the IFNγ T cell responses in sheep. In order to get further insight into the involved mechanisms, we evaluated our eGn-encoding DNA vaccine strategy in the reference mouse species. A DNA vaccine encoding eGn induced full clinical protection in mice and the passive transfer of immune serum was protective. This further supports that antibodies, although non-neutralizing in vitro, are instrumental in the protection against RVFV. Addressing eGn to DEC205 was also detrimental to protection in mice, and in this species, both the antibody and the IFNγ T cell responses were strongly decreased. Conversely when using a plasmid encoding a different antigen, i.e., mCherry, DEC205 targeting promoted the antibody response. Altogether our results show that the outcome of targeting antigens to DEC205 depends on the species and on the fused antigen and is not favorable in the case of eGn. In addition, we bring evidences that eGn in itself is a pertinent antigen to be included in a DNA vaccine and that next developments should aim at promoting the anti-eGn antibody response.